Peningkatan Kemampuan Menulis Eksposisi Melalui Teknik Umpan Balik: Penelitian Tindakan di Kelas X SMAN 56 Jakarta - Sri Yuliasih (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to improve the ability to writing eksposisi class X SMA Negeri 56 Jakarta through feedback techniques. Through feedback techniques, improvement can be seen in the process and results. This research is an action research (Action Research) This research was conducted at SMA Negeri 56 Jakarta. The subjects class X-3 totaling 35 students. Implementation of this research is divided into three cycles, each cycle will be done twice meetings. Data were obtained through (1) questionnaire, (2) field notes, and (3) documentation of student assignments and photo documentation during the learning takes place. Data analysis technique conducted with qualitative descriptive technique. Criteria for success in this study can be seen from the changes better value in each cycle. The results obtained are as follows. (1) the use of feedback techniques to improve the quality of learning in students writing eksposisi. This is shown in the increase in aspects of the process learning situation, students focus more on learning, students are also more responsive, active and creative, and learning to writing eksposisi becomes more enjoyable. (1) the use of feedback techniques can improve the results of the ability to write exposition. This is seen in the increase in the average score before the given action, namely 63.28 after a given action cycle 1 score average to 67.19 there is an increase of 3.92, second cycle average score of 74.29 there was an increase of 7, 09 and at the end of the cycle three score average to 84.17 there is an increase of 9.89. Overall at the end of the third cycle of all aspects and criteria written eksposisi has increased significantly. Based on these results, we can conclude that through feedback techniques can increase the ability to writing eksposisi class X SMA Negeri 56 Jakarta.